COMPARISON OF FILTRATION LOSS REDUCTION IN HORIZONTAL DIRECTIONAL DRILLING MUD USING RICE STRAW WITH INDUSTRIAL ADDITIVES - Terakulsatit, Bantita; Glumglomjit, Sakchai (GEOMATE Journal, 2025)
Frac-out is a prevalent challenge in Horizontal Directional Drilling (HDD), arising when drilling fluid pressure exceeds the mechanical strength of surrounding geological strata. This induces fractures, allowing fluid to escape into subsurface formations or reach the surface, thereby compromising operational efficiency and threatening nearby ecosystems. Addressing this issue, the present study explores rice straw—a cellulose- and silica-rich agricultural byproduct—as a natural additive in HDD fluids. Its performance was compared with conventional industrial additives, including Carboxymethyl Cellulose (CMC) and Lost Circulation Materials (LCM), under controlled conditions at room temperature and pressures of 20, 50, and 100 psi. Key parameters examined included fluid viscosity, filtration loss, and mud cake formation. CMC, at 0.7% concentration, exhibited optimal rheological properties with the highest viscosity and lowest filtration loss across all pressures. Rice straw at 7% concentration showed promising results in enhancing mud cake thickness and minimizing fluid loss, particularly at low pressure, though its structural stability diminished at higher pressures. LCM maintained consistent mud cake formation but had limited impact on viscosity and fluid retention. Morphological analysis via SEM revealed that composite formulations containing mixed additives improved microstructural density and filtration uniformity. These findings highlight rice straw’s viability as a cost-effective and eco-friendly alternative to synthetic additives, especially for use in moderate pressure drilling and environmentally sensitive conditions.